2015
DOI: 10.1007/s00381-015-2689-3
|View full text |Cite
|
Sign up to set email alerts
|

De novo formation of brain tumors in pediatric population following therapeutic cranial irradiation

Abstract: de novo brain tumors after irradiation has poor prognosis in neurosurgical practice. Vigilance and awareness for possibility of de novo new tumor are warranted for both families and physicians at follow-ups even years after the treatment of initial tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…The 3 years progression-free survival rate ranges from 0 to 8.7% [15,16]. Although radiotherapy and chemotherapy are considered as significant risk factors for secondary cancer, current findings do not support radiotherapy or chemotherapy withdrawal based on risk of future second tumors, since recent publications reported about a quite low rate of second brain cancer in patients treated with radiochemotherapy (0.08-1.25%) [17,18].…”
Section: Discussioncontrasting
confidence: 55%
“…The 3 years progression-free survival rate ranges from 0 to 8.7% [15,16]. Although radiotherapy and chemotherapy are considered as significant risk factors for secondary cancer, current findings do not support radiotherapy or chemotherapy withdrawal based on risk of future second tumors, since recent publications reported about a quite low rate of second brain cancer in patients treated with radiochemotherapy (0.08-1.25%) [17,18].…”
Section: Discussioncontrasting
confidence: 55%
“…Formation of secondary tumor (other than the primary tumor type) was discussed in the literature before. We have published our experience regarding second primary tumors (6). Our retrospective analysis revealed that there were 2 high-grade glial tumors arising after 6 and 11 years after radiotherapy.…”
Section: █ Discussionmentioning
confidence: 99%
“…There is a recommendation that secondary brain tumour screening by MRI should be performed annually for the initial 5 years after completion of the radiotherapy, and thereafter repeated MRI screening should be performed only for the patients with neurological symptoms, such as headache, cognitive changes and seizures, particularly in those with a history of haematological malignancy or radiotherapy at a young age [ 44 ]. However, large sample, prospective randomised studies are needed in this regard.…”
Section: Post-remission Phasementioning
confidence: 99%